An Overview of The Risk Factors for Patients with Inguinal Hernia at Aloei Saboe Hospital in Gorontalo - Potutu, Aliffa Cahya; Abdul, Romy; Kasim, Vivien Novarina A.; Pateda, Sri Manovita; Daud, Serly (Jambura Medical and Health Science Journal, 2024)
Introduction: Hernias happen when an organ or tissue bulges through a weak  point in the abdominal wall. Inguinal hernias are common and may need surgery.  The present study report the overview of the risk to affect the inguinal hernia at  Aloei Saboe Hospital.Method: The research focused on patients with inguinal hernias who underwent  examinations at Aloei Saboe Hospital, in Gorontalo Province from January to  December 2022. The study used the total sampling technique, with a sample size  of 42 individuals. It was conducted in September and October 2023 at the same  hospital.Results: The data indicates that a significant portion of patients in the range of age  56-65 years (28.6%), with a majority being male (85.7%). Additionally, the  majority of patients who were not employed (19.0%) were also found to have this  condition, as well as a vast majority of those with a primary diagnosis of inguinal  hernia (88.1%).Conclusion: Most patients with inguinal hernia at Aloei Saboe Hospital are males  in the late elderly age group who are no longer working. The main diagnosis for  most patients is inguinal hernia. The study's findings suggest that the hospital can  enhance its system, particularly in archiving medical records or electronic medical  forms, to serve its patients better. Key words: Gorontalo, hernias, inguinal hernia